2022
DOI: 10.5194/acp-22-8739-2022
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) and their alkylated, nitrated and oxygenated derivatives in the atmosphere over the Mediterranean and Middle East seas

Abstract: Abstract. Polycyclic aromatic hydrocarbons (PAHs) and their alkylated (RPAHs), nitrated (NPAHs) and oxygenated (OPAHs) derivatives are air pollutants. Many of these substances are long-lived, can undergo long-range atmospheric transport and adversely affect human health upon exposure. However, the occurrence and fate of these air pollutants have hardly been studied in the marine atmosphere. In this study, we report the atmospheric concentrations over the Mediterranean Sea, the Red Sea, the Arabian Sea, the Gul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 148 publications
1
8
0
Order By: Relevance
“…Specifically, the mean concentration of Σ 26 PAHs in the coastal marine atmosphere of southern Europe was 2.99 ± 3.35 ng m −3 , with the highest values registered in the Mediterranean Sea (mean 4.40 ng m −3 ) and the lowest in the Arabian Sea (mean 0.59 ng m −3 ). Moreover, this study 22 also found that Phe was the most abundant parent PAH, followed by Flu, Ace, Flt, and Pyr, with mean contributions of 24%, 10%, 6%, and 5%, respectively.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Specifically, the mean concentration of Σ 26 PAHs in the coastal marine atmosphere of southern Europe was 2.99 ± 3.35 ng m −3 , with the highest values registered in the Mediterranean Sea (mean 4.40 ng m −3 ) and the lowest in the Arabian Sea (mean 0.59 ng m −3 ). Moreover, this study 22 also found that Phe was the most abundant parent PAH, followed by Flu, Ace, Flt, and Pyr, with mean contributions of 24%, 10%, 6%, and 5%, respectively.…”
Section: Resultssupporting
confidence: 60%
“…A pronounced contribution of Phe to the total PAHs can be found in summer and is displayed in Fig. 3 C. It should be noted that previous studies have found a relatively high contribution of 3-ring compounds to the total PAHs in the coastal regions and offshore 22 , 44 46 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Nitrated polycyclic aromatic hydrocarbons (NPAHs) generated by the substitution of one or more hydrogen atoms in the aromatic ring of polycyclic aromatic hydrocarbons (PAHs) with nitro group (-NO 2 ) are a common type of organic nitrogen compounds in aerosol particles (Bandowe and Meusel 2017; Lammel et al 2020;Wietzoreck et al 2022). Apart from the primary emission sources such as incomplete combustion of coal, petroleum and biomass (Zhao et al 2017;Nežiková et al 2021;Zhang et al 2021), NPAHs can also be generated through the oxidation of PAHs by OH or NO 3 radical in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%